Teledermatology- A Life-Saving Experience and its Usefulness in Nepal: A Case Report - Parajuli, Niraj; Buda, Caleb; Tiwari, Sanjib (Journal of Nepal Health Research Council, 2025)
Teledermatology is a means of diagnosing and managing dermatological cases virtually using digital tools. This is an important method which has been in use in Nepal and has a lot of potential to provide quality care to the patients from the remote corners of Nepal. It has been mostly used to manage chronic dermatological conditions. Here. we report a patient, suffering from multiple painful ulcers and a steadiliyy declining quality of life, was diagnosed with pyoderma gangrenosum via mobile teledermatology. Prompt intervention based on this remote diagnosis led to successful management and significant clinical improvement. We try to put an emphasis on the mobile teledermatology that it is even useful in hard to diagnose cases and provide proper management. We also would like to highlight that this modality should be promoted and used more often to provide specialists medical services to the rural communities Nepal. Keywords: Digital dermatology; pyoderma gangrenosum; teledermatology; telemedicine.